Variables Associated With Body Image Concerns in Acromegaly Patients: A Cross-Sectional Study - Zhang, Xiaomei; Li, Yanqing; Zhong, Yueping; Wang, Ziheng (Frontiers in Psychology, 2022)
Objective: Acromegaly is often associated with altered physical as well as facial appearance. Extremely little, however, has appeared in the medical and psychological literature about body image concerns in patients with acromegaly. Our research is to find the influencing and related factors of patients' body image distress and explore the possible effects of stigma on body image concerns. Design: Cross-sectional study Methods: A total of 68 individuals with acromegaly were enrolled in our study. A total of 70 persons with nonfunctional pituitary adenomas were randomly recruited as a healthy control group. Using structured questionnaires, we explored perceived body image, Body Image Concern Inventory. We also use Hamilton Anxiety Scale, Stigma Scale for Chronic Illness, The Brief Illness Perception Questionnaire, and Short-Form-36 Health Survey to evaluate health-associated conditions, and analyze the related factors that influence body image concerns in acromegaly patients. Results: Sixty-eight persons were enrolled (31 males,37 females, 46.36±12.47years old). The body image concern score for acromegaly patients was 47.49±13.81 and NFPA was 21.10±7.44. The difference between the two groups was statistically significant. Multiple stepwise regression analysis showed that the hazard factors of the body image were sex (P=.001), age (P=.01), and Internalized stigma (P＜.000, AdjR2=0.756). Conclusions: People with acromegaly have serious body image concerns. The stigma around the disease also makes sufferers more concerned about their image. Such worries lead to poor QoL (quality of life). Doctors may need to find better ways to control their patients' hormone levels, and the nurse should provide more information on how to improve the patient's body image or find ways to reduce the patient's disturbance with body image.